Non-Formal Education Focused on the Development of Critical Thinking and Media Literacy: The Role and Activities of Key Stakeholders in Slovakia - Vrabec, Norbert; Kačinová, Viera; Kitsa, Mariana; Majda, Martin (Journal of Education Culture and Society, 2023)
Aim. This research study aims to examine the role and activities of key stakeholders in Slovakia who participate in non-formal education activities focused on the issue of critical thinking in relation to media communication. The aim was to gain an overview of the ways and means by which these actors address their target groups and what conceptual approaches they use to increase the level of media literacy at the national level.Methods. Framework analysis of secondary data on Slovak subjects whose non-formal educational activities and tools focus on the issue of critical thinking, disinformation and fake news by increasing the level of media and information literacy of various target groups.Results. The analysis of secondary data showed that representatives of various stakeholders in Slovakia offer different categories of projects and activities to increase the level of media and information literacy of various target groups. The obtained results indicate that the most active providers of non-formal education activities are in the sector of non-governmental organisations and think tanks. Our analysis also aimed to examine what types of educational activities organisations provide. The most significant representation is static online content (various types of educational content available through the website).Conclusions. The presented research results suggest that in terms of the position of key actors, the ways of their involvement in non-formal education processes are sufficiently diversified. They use a wide range of implementation concepts and models to develop critical thinking through non-formal learning methods for different target groups.